Between resistances and changes: the violence against women in the justice of Neuquén (Argentina) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
In this paper we will be analyzing, from social studies with a gender perspective, two court decisions about violence against women that were recently made in Neuquén, Argentina. The guiding purpose of this paper is to highlight the tensions –between tensions and resistances- that exist in the institutions and between the public sector (Court) and private sector (Lawyers) when interacting as agents of justice, in judicialized cases where the victims are women
Keywords: social sciences; gender perspective; violence against women; gender stereotypes; justice sector